Studying a mathematics teacher’s documentational and identity trajectories over time - Giorgos Psycharis; Charlotte Krog Skott (Journal of Mathematics Teacher Education, 2023)
We study the interactions over 22 years between one mathematics teacher and his resources for teaching, especially digital ones, with a dual focus on the teacher’s documentational and identity trajectories and professional development. We combined a theoretical framework on teachers’ work with resources  —documentational approach to didactics (DAD)— with a framework based on social practice theory—patterns of participation (PoP). The DAD analysis provided rich descriptions of which digital resources the teacher interacted with and of the transformative evolution of these interactions over time. The PoP analysis offered explanations of how and why the teacher transformed his interactions with the resources through foregrounding affective and contextual factors as significant for the teacher’s formation of identity. We conclude that the combination of the two frameworks provided deeper and complementary insights into the teacher’s long-term professional development with digital resources, and that such networking is needed to develop balanced understandings of teachers’ long-term interactions with digital resources.